Changes in concentrations of circulating heat‐shock proteins in House Finches in response to different environmental stressors. Issue 4 (December 2013) - Hill, Geoffrey E.; Fu, Xiaoyu; Balenger, Susan; McGraw, Kevin J.; Giraudeau, Mathieu; Hood, Wendy R.
ABSTRACT Heat‐shock proteins (HSP) are molecular chaperones that play key roles in the maintenance of cellular homeostasis under variable environmental conditions. Although HSP are frequently used in studies of wild vertebrates as indicators of stress, no one to date has assessed responses of HSP60, HSP70, and HSP90 in the same species to different environmental stressors. We studied changes in the circulating concentrations of HSP60, HSP70, and HSP90 in wild‐caught House Finches (Haemorhous mexicanus) in response to multiple and sequential stressful environments, including high temperatures, transportation, and pathogen exposure. House Finches sampled during a period of low‐environmental stress with moderate ambient temperatures had low levels of HSP60 and modest levels of HSP70 and HSP90 compared to birds sampled during a presumably more stressful period with high temperatures. After exposure to high‐ambient temperatures, transportation in a vehicle, and exposure to Mycoplasma gallisepticum, captive finches were found to have increasingly higher levels of HSP60. HSP70 tended to rise in response to each stressor, but to drop in the weeks between stress challenges. HSP90 levels increased significantly only in response to pathogen challenge. Our observations suggest that HSP60 and HSP70 are indices of a range of stressors in House Finches, whereas HSP90 primarily reflects health state.